Urgensi Manajemen Pembinaan Peserta Didik dalam Upaya Meningkatkan Prestasi Siswa di MAN Sampang - Munib Munib; Holipah Holipah; Moh. Faddol (LP2M Institut Agama Islam Nazhatut Thullab Sampang, 2026)
In the era of globalization, mastery of information technology is the main requirement for SMK graduates to compete in the world of work. One of the supporting facilities to improve student competence in this field is a computer laboratory. Therefore, there are two focuses in this research. First, how computer laboratory management in improving competence of students majoring in visual communication design (DKV) at SMKN 1 Sampang. Second, how the effectiveness of computer laboratory management in improving student competencemajoring in visual communication design (DKV) at SMKN 1 Sampang. This research uses a qualitative approach with the type of case study. Data sources were obtained through observation, interviews, and documentation. The informants in this study were principal, waka curriculum, head of computer laboratory, head of department, and students. Checking the validity of the data is done through extended observation, increased persistence, and triangulation. The results of this study show that: First,computer laboratory management is carried out with four functions of management, namely computer laboratory management planning which includes analyzing needs and making schedules. The organization of computer laboratories is carried out functionally because it does not yet have a special organizational structure. The implementation of practical activities in computer laboratories is carried out according to a predetermined schedule, starting with the provision of material in the class before